ML-7 attenuates airway inflammation and remodeling via inhibiting the secretion of Th2 cytokines in mice model of asthma - Huang, Chuanjun; Zhang, Zewen; Wang, Liuxin; Liu, Ju; Gong, Xiaodan; Zhang, Caiqing (Molecular medicine reports, 2018)
Previous studies have indicated that smooth muscle myosin light chain kinase (MLCK) has a prominent role in the regulation of smooth muscle contraction, which tends to be upregulated in asthma. In recent years, numerous studies have reported that MLCK is intimately connected with the immunoregulatory mechanism of T cells. The imbalance of T helper type 1 cells (Th1)/Th2 constitutes the immune‑associated pathological basis of chronic asthma. Th2‑associated cytokines, including interleukin‑4, ‑5, ‑13, ‑25 and ‑33, are involved in airway inflammation, hyperresponsiveness and remodeling, which leads to a progressive decline in lung function. The purpose of the present study was to verify whether inhibition of bronchial MLCK attenuated the expression Th2‑associated cytokines in asthmatic mice, including the above‑mentioned ones. Female BALB/c mice were used to establish an ovalbumin (OVA)‑induced model of asthma, of which one group was treated with the MLCK inhibitor (5-iodonaphthalene-1-sulfonyl) homopiperazine (ML‑7). The inhibitor of MLCK, ML‑7 attenuated airway inflammation and remodeling by reducing inflammatory cell infiltration and the secretion of Th2 cytokines in mice model of asthma, which may represent a promising therapeutic strategy for asthma.